Upaya Dinas Pariwisata Kota Samarinda dalam Pembinaan Ekonomi Kreatif di Desa Budaya Pampang - Deni Dova Anggelin; Iman Surya; Letizia Dyastari (Jurnal Ilmu Pemerintahan, 2022)
This study aims to identify and describe the efforts made by the Samarinda City Tourism Office in fostering the creative economy in the cultural village of Pampang. With a research focus, namely the development of the creative economy and the sape' music festival. This type of research uses descriptive qualitative research which conducts analysis through primary data in the form of interviews and secondary data in the form of documents related to the problems studied and this research goes directly to the field of research through observation, interviews and documentation to research sites in the Pampang Culture Village, Samarinda. The results of this study show how the efforts of the Samarinda city tourism office have formed pokdarwis (tourism awareness groups), provided coaching funds to several creative economy actors and repaired damaged facilities in the Pampang Culture village. The tourism office in this case also carries out sape' music festival activities and provides the tools and materials needed for these activities. Factors that are hindering the efforts of the tourism office in developing the creative economy at this time, namely the limited budget in implementing all programs, the readiness of the community that is not optimal and the limited facilities that make the tourism office help to improve it. In this case, good cooperation between the government and the community is needed in building and promoting the Pampang cultural village and there needs to be initiation from the community to hold more creative activities to attract visitors.